2011
DOI: 10.1371/journal.pntd.0001180
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specificity of Clinical Dengue during Primary and Secondary Infections

Abstract: BackgroundThis study aims to estimate the age-specific risks of clinical dengue attack (i.e., the risk of symptomatic dengue among the total number of dengue virus (DENV) infections) during primary and secondary infections.MethodsWe analyzed two pieces of epidemiological information in Binh Thuan province, southern Vietnam, i.e., age-specific seroprevalence and a community-wide longitudinal study of clinical dengue attack. The latter data set stratified febrile patients with DENV infection by age as well as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
63
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 44 publications
20
63
2
4
Order By: Relevance
“…The male predominance has also been reported in several other studies [6]. The mean age of patients in our study was 32.4 years which is similar to other studies where higher age groups were observed of developing symptomatic disease than younger groups [7][8][9] and contradictory to the study by Raut and Patil where they revealed children <10 years were affected more [10].…”
Section: Discussionsupporting
confidence: 85%
“…The male predominance has also been reported in several other studies [6]. The mean age of patients in our study was 32.4 years which is similar to other studies where higher age groups were observed of developing symptomatic disease than younger groups [7][8][9] and contradictory to the study by Raut and Patil where they revealed children <10 years were affected more [10].…”
Section: Discussionsupporting
confidence: 85%
“…The incidence of dengue was least in the older age groups probably in our view because of lesser outdoor activity compared to younger people. This was similar to a study performed by Amir Khan et al (5).n a study by Khoa T.D.Thai et al (6) showed that increasing age lead to increasing risk of clinical attack in both primary and secondary dengue infection. This study was done by obtaining seroprevalence of dengue specific for age and frequency of clinical attack specific for age.…”
Section: Resultssupporting
confidence: 91%
“…There are several plausible, nonmutually exclusive explanations for the decreasing severity over time. A difference in disease severity with age is a phenomenon that has been noted previously, for example, in Cuba, Thailand, and Singapore, [19][20][21][22][23] which could be consistent with the observed trends; however, we do not observe such a clear relationship with age and severity here and observe a fairly small shift in age of cases. Secondly, in 1999, a new handbook was published with recommendations for hospitalization of suspected dengue cases.…”
Section: Resultssupporting
confidence: 84%